Implementasi Asuransi Mandiri Inhealth PT. Bank Sumut : Studi Kasus PT. Bank Sumut Cabang Stabat - Alesandro Nesta; Najla Yasmin; Syafa Nazwa Almalika Saragih; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2024)
Mandiri Inhealth is a life and health insurance company that provides commercial health insurance for private companies, state-owned companies and government institutions. PT. Bank Sumut, especially the Stabat branch, is collaborating with Mandiri Inhealth to ensure the health of their permanent employees. The programs offered include inpatient care, outpatient care, childbirth, as well as assistance with medical equipment such as glasses. Apart from permanent employees, employees' immediate families also receive similar life and health insurance, although there are restrictions on certain facilities, such as medical equipment assistance which is only provided to permanent employees. This study reveals the advantages and obstacles in implementing Mandiri Inhealth at Bank Sumut Stabat Branch. The advantages found include varied insurance products, fast and targeted customer service, life insurance protection, heirs' compensation, and post-service insurance products. However, there are problems related to the referral system which create obstacles for users to access health care, because only certain services can be accessed without a referral, such as pediatricians, obstetricians and ENTs. Through interviews with the Head of Bank Sumut Stabat Branch, the company's commitment to providing optimal health protection, not only for employees but also their families, can be seen. This reflects the company's efforts to maintain the welfare and financial security of employees through the various insurance programs offered.